Secular trends in the mortality of gastrointestinal cancers across China, Japan, the US, and India: An age-period-cohort, Joinpoint analyses, and Holt forecasts - Cui, Yiran; Cheng, Gang; Tian, Gang; He, Simin; Yan, Yan (Frontiers in Public Health, 2022)
Background: Colon cancer, esophageal cancer, and stomach cancer are the common cause of morbidity and mortality in China, Japan, the U.S. and India. The current study was aimed to assess and compare secular trends of Gastrointestinal cancers mortality during the period (1990-2017) in age-specific, time period and birth cohort effects. Method: We used Joinpoint model to collect age-standardized mortality rates for four countries. And we designed an age-period-cohort (APC) analysis to estimate the independent effects on mortality of three cancers. Result: Joinpoint model shows that in addition to esophageal cancer death rate in Japan, the age-standardized mortality rate (ASMR) of esophageal cancer and stomach cancer in other countries declined rapidly. APC analysis presented a similar pattern of age effect between four countries for colon cancer and stomach cancer, which increased from 20-89 age groups. Differently, the period effect rapidly increased for esophageal cancer and stomach cancer in U.S., the period effect of China presented a declining volatility, showing its highest value in 2007. The future forecast highest mortality trends were found in China. Conclusion: Therefore, the obvious increase in colon cancer recommended that earlier tactics must be performed to reduce the mortality from specific cause from 2018 to 2027.